A política do dizer na esfera escolar: uma análise de polêmica sobre interdição de obra literária - Branquinho, Lilian (2011)
This research benefits from the studies of the Bakhtin Circle in relation to the concepts of discursive genres, field and ideology. The Russian philosopher establishes that the subject enunciates from a given field of human activity and, therefore, his/her discourse receives coercions from this same field, expressing the ideologies and the social values that circulate in them. Our analysis corpora are polemic discourses presented in the media, especially the digital one, in which the adequacy of the book Aventuras Provisórias written by Cristóvão Tezza, distributed in 2009 by the Santa Catarina State Government for public schools and used as support for reading activities and language study was polemized. The book was considered by schools as inappropriate for the age group that was destined for in order to possessing pornography content, referring to the descriptions of sexual relationships, and, consequently, the Santa Catarina State collected nearly 130 thousand copies of the work. Considering the book Aventuras Provisórias as a statement that generates responses, our aim was to make a qualitative and comparative analysis of the selected corpora in the media in order to investigate what can be said in school, reflecting on the ideological values that are materialized and refracted in the school field. We understand that this controversy generated around the Tezza‘s literary work is due to the displacement of a statement belonging to the literary field to the school field, that is, when changing to the school field, the literary statement is considered inappropriate, especially, in the face of their lexical choices and composition manner. In the analyzed discourses, we found that what seems to motivate the interdiction on the literary work considered "pornographic" by the school field is the difficulty that the school and its staff have in dealing with sexual themes. Thus, the intolerant discourses can be referred to the social place where the subject enunciates: the closest and most involved in the school routine, more intolerant discourses are.